Transient changes in aromaticity and their effect on excited-state proton transfer reactions. Issue 19 (4th May 2022) - Arpa, Enrique M.; Durbeej, Bo
Abstract : Quantum chemical modelling shows that energy barriers for excited-state proton transfer reactions involving 2-pyridone are governed by the transient onset of antiaromaticity upon interaction between the photoexcited state and a second excited state. Abstract : The common approach to investigate the impact of aromaticity on excited-state proton transfer by probing the (anti)aromatic character of reactants and products alone is scrutinized by modelling such reactions involving 2-pyridone. Thereby, it is found that energy barriers can be strongly influenced by transient changes in aromaticity unaccounted for by this approach, particularly when the photoexcited state interacts with a second excited state. Overall, the modelling identifies a pronounced effect overlooked by most studies on this topic.